Drop Everything and Sing the Music: Choristers' Perceptions of the Value of Participating in a Multicultural South African University Choir. Issue 1 (2nd January 2019) - Barrett, Michael; Vermeulen, Dorette
Abstract: This case study explored the perceptions of choristers singing in a multicultural university choir in South Africa and the personal value they associate with their choir participation. Data were collected through semi-structured individual interviews, focus groups, and a four-month period of observations of choir rehearsals and performances. This research highlights the multidimensional experiences of choral singing which can be fulfilling, abundant, as well as demanding at times. Emergent themes include music as a key indicator leading to personal-, resilience-, and social values. Findings indicate the significance of collective music making and the ways in which it influences the lives of participants, such as enjoyment, health benefits, achievement, commitment, accountability, a sense of belonging, and camaraderie. Choristers experience the choir environment as safe and conducive to forming important relationships. Although cultural integration takes place to a large extent, there are still barriers due to a variety of languages within a diverse group of choristers. Participants' reflections reveal that choir participation is an ideal vehicle whereby social cohesion can be enhanced. Finally, the study highlights the importance of choral conductors and educators employing strategies that allow choirs within a multicultural environment to successfully transform in order to remain relevant to the needs of the singers within a diverse setting.